AHP-SWARA Implementation Method for Evaluation and Selection Employee Promotion - Akmaludin, Akmaludin; Suriyanto, Adhi Dharma; Widianto, Kudiantoro (Politeknik Ganesha Medan, 2025)
The evaluation process of employee selection is very important for organizations that want to carry out quality leadership, the purpose of this study is to objectively prove the results of the selection of job promotions that have been evaluated continuously every time leadership occurs. The evaluation results of the leadership selection process become routine, so that the results of leadership promotions can provide improvisation to organizations that are increasingly advancing towards future leadership targets. The proposed method for the evaluation and selection process uses the Analytic Hierarchy Process (AHP) and specifically Stepwise Weight Assessment Ratio Analysis (SWARA). Both of these methods utilize expert intervention in providing input in providing assessments of multi-criteria and alternatives. So that the priority of the criteria is carried out by an index process similar to that owned by the two methods, thus providing more optimal results for decision-making support. The assessment of the results requires seven criteria and twenty-four alternatives. The results obtained require two index processes for both criteria and alternatives. The first rank is determined by the weight of the calculation results of the seven criteria and alternative assessments from experts. The first rank of twenty-six employees was given to K20 with a weight of 0.932 and followed by K2 with a weight of 0.08. Thus, job promotion can be developed with a double index that can provide optimal results in supporting job promotion decision making